THE ROLE OF ETHNOCENTRISM IN BUYING PROCESS OF THE DOMESTIC PRODUCT - Noor, Dewantika; Haryanto, Budhi (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The increase trend of globalization and advance technology in communication and transportation enable the consumers to access great variety of products and services from other countries. The competition between domestic and foreign corporations became interesting to be studied.The objective of this researchexplains the relationship among of the observed variables. There are six relationship, namely, perceived quality and price fairness toward consumer attitudes toward domestic product, consumer attitudes toward intention to buy domestic product. Last, role of ethnocentrism as the moderation in this research. The data is collected by survey and guided by questionnaire to 250 respondents. The survey is conducted in Yogyakarta by using a convenience sampling method. The constructed model were measured using five point Likert scale. The findings show that consumer attitudes toward Leather Bag in Manding is influenced by price fairness and perceived quality.In the relationship between perceived quality, price fairness, consumer attitudes, and intention to buy, the ethnocentrism did not play a moderation role.